National Education Plans: hopes and contradictions - Bigarella, Nádia; Carvalho, Janine A. Barthimann (Série-Estudos, 2020)
This paper is the result of studies carried out in the masters in education. It aims to discuss the trajectory of educational plans, gathering important elements that explain its historical constitution and the importance of the participation of society in the choice of public educational policies implemented in the different periods delimited in this text. This research, based on documentary sources, has shown a contradictory link between economic planning and educational plans, which are important documents for the organization of education systems. The National Education Plans, as a state policy, did not take place, remaining like another document that expresses intentions for educational area.